Determinants of Internal Audit Effectiveness in Indonesian Public Sector - Yulia Dela Dacrea; Ancella Anitawati Hermawan (Yayasan Riset dan Pengembangan Intelektual, 2024)
Indonesia is one of the countries that supports the role of internal auditors in government. This study aims to investigate the determinant factors that can be associated with the effectiveness of internal audits in the public sector. A survey was conducted among 142 internal auditors from 60 Ministries and Agencies in Indonesia. Data analysis and hypothesis testing were carried out using Structural Equation Modelling (SEM) in the Smart-PLS application. This study reveals that the audit committee, internal audit competence, the role of external audit, and top management support are variables that determine the effectiveness of the internal audit. The findings of this study could have implications for strengthening the formulation of regulations related to auditing, especially regarding the establishment of audit committees in the public sector. It also enriches previous studies by adding public sector audit committees as one of the determinants of internal audit effectiveness, where their presence is considered still uncommon in the public sector in Indonesia